Daddy's gone a hunting [large type] - Clark, Mary Higgins (Thorndike Press, 2013)
When her sister is wrongly implicated in an explosion that has destroyed her family's priceless antiques business and killed an employee, Hannah struggles to find clues in the ashes and discovers a life-threatening secret from the past.